Análise da viabilidade técnica e econômica de processar o gás natural paravenda em plataformas de campos de gás retrógrado offshore - Marina Maciel Dias de Souza (2017)
The development of non-associated gas fields offshore can be considered stranded in remote areas, quite distant from the coast or without processing infrastructure onshore. This is a result of the lower natural gas price compared to other hydrocarbon products such as liquefied petroleum gas (LPG), ethane and nafta, for example. Therefore, production development projects in these cases should consider other configurations to enable the production. The onshore infrastructure requires a high investment and constitutes the natural gas specification according to resolution ANP Nº 16 de 2008 of the brazilian national agency (ANP) for its transport, sales and consumption. If it were possible to specify the gas as well as the condensate in the production platform, the investment costs could be lower, enabling the production of a field before considered stranded. In this scenario, the objective of this work is to economically and technically evaluate the feasibily of introducing additional systems of gas processing offshore, in comparison to the standard option of treating the gas offshore and processing onshore, for a non associated retrograde gas field. The cost estimates software QUE$TOR® was used for the economic comparison. The technicalfeasibility was accessed through the process simulator Aspen HYSYS®, considering three similar processes to those used in onshore processing units for dew point adjustments, such as Joule-Thomson valve, turboexpansion and refrigeration cycle. The economic results were promising but strongly related to gas price. The simulation results preliminaries indicated that the use of the three dew point treatments are viable but depend on the feed gas composition